Using narrative exposure therapy to treat women with a history of intimate partner violence for post-traumatic stress: a series of single case studies - Lane, Stephanie (2019)
Background: Intimate Partner Violence (IPV) is said to affect one in four women and is therefore a human rights concern in the UK and internationally. Post-traumatic stress (PTS) is the most prevalent adverse psychological outcome associated with IPV. The impact of IPV can be unique; survivors’ sustained exposure to multiple traumatic events can result in psychological parallels to being taken hostage and subjected to torture. However, interventions often focus on risk management, and few treatments are suited to the chronicity and complexity of trauma endured in IPV. Narrative Exposure Therapy (NET), a treatment specifically designed to alleviate PTS following exposure to multiple trauma, has recently been included in NICE guidelines.